The Turks and their language in the Romanian language and linguistic awareness (an outline of the issues) - Cychnerski, Tomasz (Balcanica Posnaniensia. Acta et studia, 2003)
This article attempts to provide a general overview of the linguistic influences of Turkic peoples on the Romanian language, presented in a diachronic order consistent with the course of historical events. The aim of the study was to show the extent and nature of Turkish influences on the Romanian language system (lexicon, phraseology, morphological elements) and on the linguistic awareness of Romanians, reflected in the secondary meanings of ethnonyms, phraseologisms and proverbs. The author drew on the work of classics of Romanian Turkology and linguistics, such as Lazăr Șăineanu, Vladimir Drimba and Emil Suciu, as well as etymological and toponymic data. The main findings of the study indicate that the greatest influence of the Turkish language took place during the period of Ottoman domination (14th–19th centuries), when Turkisms accounted for as much as 17% of Romanian vocabulary. Borrowings covered almost all areas of everyday life, and some of them are still used in general Romanian today. The article also considers the influence of Turkish on Romanian phraseology, word formation and onomastics. In turn, the analysis of secondary meanings and phraseology related to the ethnonym ‘Turk’ reveals mainly negative historical connotations resulting from the experience of Ottoman occupation. Today, the influence of Turkish on the Romanian language is minimal, with many old borrowings having been naturally eliminated or replaced by elements of Romance origin.